Digital electronics : principles and applications - Roger, Tokheim; Tokheim, Roger (London, United Kingdom : McGraw Hill Education, 2014)
Provides an approach to digital electronics. This title includes knowledge of electrical theory and principles and at a level that allows students with limited math and reading skills can gain a clear understanding of concepts and application covered in a digital electronics course.
Ch. 1 Digital ElectronicsCh. 2 Numbers We Use in Digital ElectronicsCh. 3 Logic GatesCh. 4 Combining Logic GatesCh. 5 IC Specifications and Simple InterfacingCh. 6 Encoding, Decoding, and Seven-Segment DisplaysCh. 7 Flip-FlopsCh. 8 CountersCh. 9 Shift RegistersCh. 10 Arithmetic circuitsCh. 11 Memory and StorageCh. 12 Digital SystemsCh. 13 Computer SystemsCh. 14 Connecting with Analog Devices
Includes bibliographical references and index.
Keywords: DIGITAL ELETRONICS -- TEXTBOOKS